Effects of low temperatures and cryogenic freeze-thaw cycles on concrete mechanical properties: A literature review. (22nd August 2022) - Lin, Hongwei; Han, Yanfeng; Liang, Siming; Gong, Fuyuan; Han, Song; Shi, Changwei; Feng, Peng
Highlights: The compressive and tensile strength of concrete are improved at low temperatures. The stress–strain behavior of cryogenic concrete is more brittle than normal concrete. The moisture content has a great influence on the behavior of cryogenic concrete. The cryogenic freeze–thaw cycles can result in severe damage of concrete. Abstract: In recent years the application of concrete material in environment with very low temperatures is on the rise. However, systematic knowledge on the mechanical behavior of concrete at low temperatures are not readily available for most researchers and engineers. In the 1970s to 1980s the cryogenic behavior of concrete was intensively studied by researchers from western countries, but after that relevant research activities decreased until it regains researchers' interests in recent years. Boosted by the rapid development of economy in China, Chinese researchers start to focus on this topic again and have contributed some new knowledge in this respect. To help researchers and engineers design, analyze and construct concrete structures in the cryogenic environment, this paper presents a literature review on the mechanical properties of concrete subjected to low temperatures and cryogenic freeze-thaw cycles. First the effects of low temperatures on the main properties of concrete including compressive strength, tensile strength, elastic modulus, etc., are reviewed and the existing mathematical models are summarized and compared. In the second part, the concrete damage induced by cryogenic freeze-thaw cycles is discussed, and emphasis is put on the mechanism of cryogenic freeze-thaw damage. The complied conclusions by the review paper can facilitate and safeguard the application of concrete structures at very low temperatures.